Analisis Off Street Parking dan Pengaruhnya Terhadap Kinerja Ruas Jalan T. Panglima Nyak Makam (Studi Kasus Sta 1 + 440 – Sta 1 + 740 Menuju Arah Simpang BPKP) - Faisal, Ruhdi; Pratama, Desky Aulia; Lulusi, Lulusi; Saleh, Sofyan M. (Journal of The Civil Engineering Student, 2022)
T. Panglima Nyak Makam Street, which is located in Banda Aceh City, has a six-lane type – two directions and a median (6/2D), but in the field it only has four – effective lanes and a median (4/2D). This road has become an economic area so that the road has been built several Off street parking. During peak hours there are often delays caused by vehicles entering and leaving off street parking. Another problem that occurs is that in the weaving section there is a large enough volume of braid current, causing a decrease in road speed and capacity. This study aims to analyze the need for off-street parking, to determine the effect of roadside activities on road performance. Based on the results of data processing, it was found that the parking index for light vehicles was 0.79 and for motorcycles was 1.15. The degree of saturation of the T. Panglima Nyak Makam Street is 0.41 for the direction to T. Nyak Arief Street and the degree of saturation is 0.36 for the direction to the BPKP Intersection.